SEMANTIC AND PRAGMATIC FEATURES OF PROPER NOUN TRANSLATION IN DIPLOMATIC DISCOURSE - Jalilova Dilbar Mansur qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Proper nouns play a significant role in diplomatic discourse because they identify countries, institutions, political leaders, international organizations, and culturally specific entities. The translation of proper nouns in diplomatic texts requires not only linguistic accuracy but also sensitivity to political, cultural, and pragmatic factors. This study examines the semantic and pragmatic features of proper noun translation in diplomatic discourse. It explores various translation strategies, including transliteration, transcription, calque, and adaptation, and analyzes how these methods affect meaning and communicative intent. The research highlights the importance of preserving referential accuracy while ensuring the target audience correctly interprets diplomatic messages. The findings demonstrate that successful translation of proper nouns contributes to effective international communication, intercultural understanding, and the maintenance of diplomatic relations.